The effect of Ramadan fasting on physical performances, mood state and perceived exertion in young footballers - Chtourou, H.; Hammouda, O.; Souissi, H.; Chamari, K.; Chaouachi, A.; Souissi, N. (Asian Journal of Sports Medicine, 2011)
Purpose: This study was designed to assess the effects of Ramadan fasting on the profile of mood state and perceived exertion in young soccer players and aerobic and anaerobic performances during the Yo-Yo, repeated sprint ability (RSA) and the Wingate tests. Methods: Twenty junior male soccer players completed the Yo-Yo, the RSA, and the Wingate tests on three different occasions: one-week before Ramadan (BR), the second week (SWR) and the fourth week (ER) of Ramadan. The total distance (TD) covered and the estimated maximal aerobic velocity (MAV) during the Yo-Yo test were recorded. During the RSA test, peak power (PP) during each sprint, the percentage of decrement of PP (PD) and total work (Wtotal) were calculated. During the Wingate test, peak (Ppeak) and mean (Pmean) powers and fatigue index (FI) were recorded. Results: TD and MAV (P=0.01) during the Yo-Yo test and PP (P=0.01, P=0.004, P=0.001, P=0.01, P=0.03 for sprints 1, 2, 3, 4, and 5, respectively) and Wtotal (P=0.02) during the RSA test were significantly higher during BR than ER. Furthermore, muscle fatigue during the RSA test increased significantly from BR to ER (P=0.01). Ppeak and Pmean during the Wingate test decreased significantly from BR to SWR and ER (P<0.0005). FI was higher during SWR (P=0.001) and ER (P<0.0005) than BR. In addition, rating of perceived exertion scores and fatigue estimated by the profile of mood state questionnaire were higher during Ramadan in comparison with BR. Conclusions: The present study suggests that both aerobic and anaerobic performances during the Yo-Yo, the RSA and the Wingate tests were affected by Ramadan fasting in young soccer players.